Optimized use of ferric chloride and sesbania seed gum (SSG) as sustainable coagulant aid for turbidity reduction in drinkingwater treatment - Chua S.-C.; Chong F.-K.; Malek M.A.; Mustafa M.R.U.; Ismail N.; Sujarwo W.; Lim W.; Ho Y.-C. (MDPI, 2023)
coagulation; drinking water; extraction method; inorganic compound; methodology; response surface methodology; sesbania; turbidity; Sesbania